Pengaruh Sumber-Sumber Kekuasaan Terhadap Politik Organisasi - Lilik Yarkoni; Khoiruddin; Muzajjad; Muhammad Mudjib Musta‟in (Journal of Public Power, 2018)
The study aims to enhance the understanding of organizational political behavior through sources of power. The research subjects were 138 sub-district office staff and village offices. Organizational political behavior and sources of power are measured by questionnaires scaled. The data of research variables were analyzed by multiple regression analysis. The results of the analysis show: (1) F = 9,841, R = 0,478, R2 = 0,228, and p = 0,000 (p <0,01), legitimate power, reward power, expert power and referent power simultaneously have positive and highly significant effect on organizational political behavior with 22.8% contribution; (2) Regression coefficient of legitimate power = - 0,036 and p = 0,994 (p> 0,05), indicating legitimate power has no effect on organizational political behavior; (3) The regression coefficient of reward power = 0,983 and p = 0,000 (p <0,01) show the reward power very significantly have positive effect on the political behavior of the organization; (4) Regression coefficient of expert power = 1,331 and p = 0.016 (p <0.05) indicates that expert power significantly affects positively on organizational political behavior, and (5) Regression coefficient of referent power = - 0.128 and p = 0.697 (p> 0.05) indicates that referent power has no effect on the organization's political behavior. Research is discussed in the context of organizational behavior.